2011
DOI: 10.1159/000332925
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Hematoma of the Pulmonary Artery and Hemopneumomediastinum after Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration

Abstract: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a safe and effective technique for the sampling of mediastinal and hilar adenopathies. We describe the first reported case of pulmonary artery intramural hematoma after EBUS-TBNA puncture of this artery. The complication was visualized by ultrasound and resolved spontaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…[5][6][7][8][9]12,14 The incidences of complications may vary depending on several factors. First, follow-up of patients to detect possible complications is not often a routine procedure, and lack of documentation is also an important factor, especially for minor complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9]12,14 The incidences of complications may vary depending on several factors. First, follow-up of patients to detect possible complications is not often a routine procedure, and lack of documentation is also an important factor, especially for minor complications.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the investigations and case reports reported in the literature, infectious complications constitute a significant proportion of serious complications ( [5][6][7][8]12,[17][18][19] ). In our series, all 5 serious complications were infections.…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review of 14 articles reported no complications [2]. The complications described in the literature have been minor bleeding [3], pneumothorax [1,4], intramural hematoma [5], pneumomediastinum [6], hemopneumomediastinum [5], bacteremia [7] and mediastinitis [8]. Steinfort et al [7] reported a 7% incidence of bacteremia following EBUS-TBNA, comparable to that detected after conventional bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…EBUS-TBNA is also a safe procedure [43], but with the rapidly increasing number of procedures it is not surprising to read occasional reports of serious complications, such as pneumothorax requiring chest tube drainage [8], infection of bronchogenic cyst [46], empyema, lung and/or mediastinal abscess [47,48], haemopneumomediastinum [49] and even death [13].…”
Section: Convex Probe Ebus For Mediastinal Nodal Staging (N-factor)mentioning
confidence: 99%